Demographic Evaluation of Oro-Dental Self-Injury for Insurance Deception; Evaluation of the Cases Referred to Shiraz Forensic Medicine Center - Mohammad Mehdi Shokouhi; Mohammad Zarenezhad; Saeid Gholamzadeh; Fereshte Sobhnamayan; Mohammad Javad Talebi; Abbas Abbaszadegan (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Nonsuicidal self-inflicted injuries are socially unacceptable and may cause mild to severe damages. Purpose: This study aimed to evaluate the demographic features of the subjects with orodental self-injuries referred to a forensic medicine center in Shiraz, Iran. Materials and Method: This cross-sectional study evaluated 51 participants (49 men and 2 women) with orodental injuries referred to forensic medicine administration. Orodental self-injury was detected in the subjects, based on the last forensic criterion of self-injuries, considering their history, clinical examinations, and panoramic radiographs. Results: The findings of this study revealed that dental self-injuries were more prevalent among married men from urban areas with secondary education levels. Most of the cases were due to the monetary compensation received. In the majority of cases, a hard object was used for this self-injury. Moreover, no statistical association was observed between the economic status and orodental self-injury. Conclusion: This study concluded that dental self-injury could be regarded as an unplanned incident because no significant correlation was observed between the participants, their economic status, and the type of dental trauma. Furthermore, detailed investigations on the latent variables are required.